KESADARAN LINGKUNGAN HIDUP MENUJU INKLUSI SOSIAL MASYARAKAT SADAR HUKUM - Zegovia Parera; Salvadoris Pieter; Mulyadi Alrianto Tajuddin (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2022)
Merauke Regent’s Regulation Number 23 of 2019 concerning Reducing the Use of Plastic Bags, is hoped that it can support environmental sustainability in Merauke Regency. However, the regulation on handling transparency has not been fully endorsed by good cooperation from the community and business actors. The purpose of this study is to analyze how the effectiveness of plastic waste control is to support environmental sustainability in Merauke Regency. The research method used is Empirical Law research, in addition to studying the law theoretically or normatively, it also examines the law in its implementation. The results of the research can be stated that the regulations for controlling plastic waste as outlined in the Merauke Regent Regulation Number 23 of 2019 concerning Reducing the Use of Plastic Bags have been complied with and implemented properly by modern shop and supermarket business actors, however this regulation has not been complied with and implemented properly by restaurants/restaurants/cafes/food vendors and traditional markets. The need for socialization and law enforcement against Merauke Regent Regulation Number 23 of 2019 concerning Reducing the Use of Plastic Bags, especially for restaurant/restaurant/cafe/food sellers and traditional market business actors.